2020
DOI: 10.21203/rs.2.18242/v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immune activation of murine RAW264.7 macrophages by sonicated and alkalized paramylon from Euglena gracilis

Abstract: Background: Euglena is a new super health food resource that is rich in the natural polysaccharide paramylon, a linear β-1,3-glucan with various biological activities including activity on the immune system in different cell lines and animals. Despite these reports, the immune regulation mechanism of paramylon is still unclear. Results: We investigate the signaling pathways paramylon impacts in immune macrophages. In RAW264.7 macrophages, sonicated and alkalized paramylon oligomers up-regulated inducible nitri… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The paramylon itself is a recalcitrant substrate, however different pretreatment methods have been reported to obtain soluble β-1, 3-glucans ( Gissibl et al., 2019 , Kusmic et al., 2018 ). The paramylon treatment with sodium hydroxide is known to reduce the degree of polymerization ( Guo et al., 2020 ) and also yield soluble nanofibers ( Kataoka et al., 2002 ). These soluble nanofibers have been shown to enhance stimulation of leucocytes and hepatoprotection because of the formation of more bioactive single helices ( Kusmic et al., 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The paramylon itself is a recalcitrant substrate, however different pretreatment methods have been reported to obtain soluble β-1, 3-glucans ( Gissibl et al., 2019 , Kusmic et al., 2018 ). The paramylon treatment with sodium hydroxide is known to reduce the degree of polymerization ( Guo et al., 2020 ) and also yield soluble nanofibers ( Kataoka et al., 2002 ). These soluble nanofibers have been shown to enhance stimulation of leucocytes and hepatoprotection because of the formation of more bioactive single helices ( Kusmic et al., 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…These soluble nanofibers have been shown to enhance stimulation of leucocytes and hepatoprotection because of the formation of more bioactive single helices ( Kusmic et al., 2018 ). In a recent study, alkali treated paramylon has been shown to activate the immuneresponse in murine RAW264.7 cells ( Guo et al., 2020 ). The SEM of soluble paramylon clearly depicts the opening of the paramylon granules ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%